Biodiversidad de parasitoides en huevos de Tibraca limbativentris Stal, 1860 en el cultivo de arroz (Oryza sativa L.) en el cantón Babahoyo, Los Ríos - Latacela Ramos, Jhony Joan (2023)
The objective of this study was to evaluate the biodiversity of parasitoids in eggs of T. limbativentri (Stal, 1860) in rice (O. sativa L) in Babahoyo, Los Ríos. The research was carried out in two phases: field and laboratory. Fifty egg clutches of T. limbativentris (Stal, 1860) were collected from rice plants at the beginning of tillering, maximum tillering and swarming stages. Eggs were collected in three rice-growing areas of Babahoyo canton: Palmar, Los Silos and Recinto San Vicente. The collected egg postures were taken to the Entomology Laboratory of the Faculty of Agricultural Sciences of the UTB, where they were incubated in Petri dishes with moistened cotton until the parasitoids were expected to emerge. For the analysis of the number of hosts and diversity of parasitoids, an analysis using descriptive statistics was applied after identification. Through the results obtained, it was determined that in the rice zones: Los Silos, Palmar and San Vicente of Babahoyo canton, the number of eggs collected was 1589 (n = 50 postures), with an average posture of 520.82 ± 71. 66, with a parasitism percentage of 2.89 %, in which the total number of parasitoids identified were: Trisssoclus sp. with 47.83 % (n = 22), followed by Telenomus sp. with 26.09 % (n = 12) and the Eulophidae family with 26.09 % (n = 12). The parasitoid Trisssoclus sp. (Ashmead, 1893) exerted significant parasitism on T. limbativentri eggs compared to Telenomus sp. (Haliday, 1833) and the family Eulophidae (Westwood, 1829) in the evaluated areas.